Enhanced thermoelectric figure of merit in Bi-containing Sb2Te3 bulk crystalline alloys. (March 2020) - Adam, A.M.; El-Khouly, A.; Novitskii, A.P.; Ibrahim, E.M.M.; Kalugina, A.V.; Pankratova, D.S.; Taranova, A.I.; Sakr, A.A.; Trukhanov, A.V.; Salem, M.M.; Khovaylo, V.
Abstract: In the present work, the structural and thermoelectrical properties of Sb2-x Bix Te3 samples prepared by the usual melting method were studied. The samples were milled, pressed and then annealed under vacuum for 3 h at 250 °C. Investigations of the microstructure and surface morphology were carried out using X-ray diffraction analysis, scanning electron microscopy and energy-dispersive X-ray spectroscopy. The Seebeck coefficient and electrical and thermal conductivities were measured from 300 to 473 K. Thermopower data indicated a p-type conduction in the samples. Structural defects were present in Sb2 Te3 during Bi addition, acting as scattering centers and leading to a decrease in thermal conductivity, thus increasing the thermopower and power factor. The power factor showed its maximum value of around 24.7 μW/cm K 2 for the sample containing the highest Bi content. High figure of merit of 1.14 was recorded for the same sample, indicating that the Bi-containing Sb2 Te3 and the related alloys are promising materials for more efficient thermoelectric devices. Highlights: Polycrystalline alloys of Sb2-x Bix Te3 prepared by direct melting of pure elements. Thermoelectric properties were measured in a wide temperature range of 300–573 K. Bi addition to the binary Bi2 Te3 system notably reduced the thermal conductivity. The Bi addition also significantly increased Seebeck coefficient and power factor. ZT of 1.14 for Sb1.65 Bi0.35 Te3 at 425 K suggests potential use at range 350–470 K.